India and Russia in Central Asia: Growing Convergence of Interests? - Athar Zafar (Vestnik MGIMO-Universiteta)
Over the decades, the partnership between India and Russia has grown stronger, enabling them to undertake combined efforts for development and engagement in neighbouring regions and beyond. Central Asia, which is a common neighbourhood of both India and Russia, has historically and culturally had close relations with the two countries. Given India's status as a major rising economy and Russia's powerful presence with deep ties to the region, the two countries can work together to deepen engagement with Central Asia. The region has high economic, political, connectivity and cultural potential, and its significance has increased amidst the current international political and economic turmoil. This paper aims to identify the areas of convergence between India and Russia for practical cooperation both at the bilateral and regional levels to further strengthen their ties and contribute to the development of their common neighbourhood. Bilateral cooperation between India and Russia in Central Asia has great potential and is of significant interest. Trilateral cooperation of India and Russia with Central Asian republics has not been extensively researched and could emerge as a new area of interest. The paper explores this phenomenon in the context of economic and educational cooperation among the three sides, which can provide another anchor for regional stability, not only in Central Asia but also in the wider region.